The usage of psychotropicand psychostimulant drugs by students during exams - Korolova, N.D.; Chorna, V.V.; Gumeniuk, N.I.; Angelskaya, V.Yu.; Hlestova, S.V. (Environment & Health, 2019)
This article includes questions about the usage of psychotropic and psychostimulant drugs by medical students during exams and its impact on the health of young generation. Objective: to analyze the characteristics of the impact of psychotropic and psychostimulant drugs on medical students of 2-6 course in Vinnytsia National Pirogov Memorial Medical University. Materials and methods: we have created a questionnaire which included 8 questions. With the help of what the survey was carried out. 358 people was involved in the survey, from which 55.1% (197) are female and 44.9% (161) are male. Results. It is worth noting that the usage of antidepressants have unequal prevalence among medical students in different courses of study.Among the students of the 2nd year, the students at least once used psychotropic drugs - 44.4%, at the third course - 63.6%, at the fourth - 36.2%, at the fifth - 50.2 %, on the 6th - 50.0%.The frequency of taking psychotropic drugs in time was: 50.0% of students used drugs before exams, 22% - after exams, 16.3% - constantly, 11.4% - "took like medical treatment ". Conclusion. Among the students we interviewed, 48% of people took nootropies, antidepressants, or a combination of them.The largest percent of consumers (63.6%) accounted for third-year students most of them was female (67%), sixth-year students (50.2%), with whom 71% were male.Probably it is connected with heavier mental pressure before testing at third and fifth courses and state exams at the 6 course.